The use of scientific biography reconstruction method in librarianship studying - M. N. Kolesnikova (Библиосфера)
The experience of the using the scientific biography reconstruction method for studying a personality within a library science investigation is described. For the first time the technique of a «linear-mine» structuring and presenting the material on a person in a dissertational research is shown.